2009
DOI: 10.1002/stem.51
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Progenitor Cells Tracked Down by Side Population Dissection

Abstract: The pituitary gland represents the endocrine core, governing the body's hormonal landscape by adapting its cellular composition to changing demands. It is assumed that stem/ progenitor cells are involved in this remodeling. Recently, we uncovered a candidate stem/progenitor cell population in the anterior pituitary. Here, we scrutinized this ''side population'' (SP) and show that, unexpectedly, not the subset expressing high levels of ''stem cell antigen-1'' (Sca1 high ) but the remainder non-Sca1 high fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
222
5
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(253 citation statements)
references
References 58 publications
(213 reference statements)
22
222
5
4
Order By: Relevance
“…Cell debris was removed by centrifugation through a 3% BSA layer. The resulting cell pellet was resuspended in pituitary-optimized, serum-free chemically defined medium (SFDM, Life Technologies; supplemented with 0.5% BSA; Chen et al 2005Chen et al , 2009 for further analyses.…”
Section: Dissociation Of Human Pituitary Adenomas Into Single Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell debris was removed by centrifugation through a 3% BSA layer. The resulting cell pellet was resuspended in pituitary-optimized, serum-free chemically defined medium (SFDM, Life Technologies; supplemented with 0.5% BSA; Chen et al 2005Chen et al , 2009 for further analyses.…”
Section: Dissociation Of Human Pituitary Adenomas Into Single Cellsmentioning
confidence: 99%
“…Mice were kept or bred in the KU Leuven Animal Facility under The pituitary was isolated from killed mice as previously described (Chen et al 2005(Chen et al , 2009). The anterior lobes (anterior pituitary (AP)) of the Drd2 K/K mice that grow prolactinomas (from 6 to 14 months of age; Cristina et al 2006) and those of the respective control mice (Drd2 C/K and Drd2 C/C ) were dispersed into single cells using collagenase type IV as explained in the previous sections for human pituitary adenomas.…”
Section: Isolation and Dissociation Of Mouse Pituitariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have reported the presence of putative CSCs in human pituitary adenomas and from mouse pituitary tumour models Xu et al 2009;Donangelo et al 2014;Lloyd et al 2013;Mertens et al 2015;Orciani et al 2015;van Rijn et al 2013;Yunoue et al 2011;Hosoyama et al 2010). It remains unknown if CSCs arise from PSCs, although their properties can be similar; for example, both are capable of in vitro self-renewal and differentiation and PSCs are likely to be chemoresistant like CSCs, since PSCs are found within the 'side population' generated by dye efflux, utilising the same transporter properties as chemoresistance (Chen et al 2009). …”
Section: Stem Cells and Pituitary Tumoursmentioning
confidence: 99%
“…The second population was characterized by marker expression similar to stem cells of other tissues (Sca1, Nanog and Oct4) and could form floating spheres (Chen et al 2005). In later studies, the same research group showed that there was enrichment in this population for the expression of SOX2, SOX9, CD44 and CD133 (Chen et al 2009). …”
Section: Introductionmentioning
confidence: 97%